Maf1 limits RNA polymerase III-directed transcription to preserve genomic integrity and extend lifespan. Issue 3 (1st February 2021) - Noguchi, Chiaki; Wang, Lucy; Shetty, Mihir; Mell, Joshua Chang; Sell, Christian; Noguchi, Eishi
ABSTRACT: A key to longevity assurance is the nutrient-sensing mTOR pathway. Inhibition of mTOR extends lifespan in a variety of organisms. However, the downstream effectors of the mTOR pathway for lifespan regulation are elusive. In a recent report, we described the role of Maf1 as a critical lifespan regulator downstream of the mTOR pathway in fission yeast. Maf1 is the master negative regulator of RNA polymerase III-directed transcription (e.g. tRNAs and 5S rRNAs) and is regulated by mTOR-mediated phosphorylation. We demonstrated that Maf1 is required for lifespan extension under calorie restriction or when mTOR is inhibited. We also showed that Maf1 prevents DNA damage at tRNA genes, which appears to contribute to lifespan maintenance by Maf1. Here we highlight these observations and present additional results to discuss the role of the mTOR-Maf1-Pol III axis in promoting genomic integrity in the face of DNA replication-transcription conflicts in order to maintain normal lifespan.